Blood tests in tired elite athletes: expectations of athletes, coaches and sport science/sports medicine staff - Fallon, K. E. (British Journal of Sports Medicine, 2007)
Background: The issue of the expectations of elite athletes, their coaches and non-medically qualified athlete support staff of consultations with sports physicians has not been previously dealt with in the sports medicine literature. As fulfilment of expectations of the content of a consultation may influence patient`s satisfaction and clinical outcome, it is important to assess the expectations of athletes and, most importantly, coaches.